2018
DOI: 10.3390/app8091624
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Polariton Triggered Generation of 1D-Low Spatial Frequency LIPSS on Fused Silica

Abstract: We report on the generation of low spatial frequency laser-induced periodic surface structures along straight lines on fused silica by spatially scanning the laser parallel to its polarization direction. The influence of the applied laser fluence and the scanning speed on the periodic surface structures is investigated. The parameter study shows that periodic structures appear in a limited parameter regime of combined fluence and scan speed with periodicities smaller than the laser wavelength. Most strikingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Self-organized structures called laser-induced periodic surface structures (LIPSS) have recently been discovered; the periods of such structures can be maintained constant and on the sub micro scale [8], and thus these structures could afford a new strategy for easy and cost-effective grating fabrication. In addition, LIPSS could be fabricated on virtually all materials, including metals [9], semiconductors [10], and dielectrics [11], which considerably expands the application range of gratings. Several parameters limit application of LIPSS, including uniformity, orientation, periodicity, and large-area consistency.…”
Section: Manipulation Of Lipss Orientation On Silicon Surfaces Using mentioning
confidence: 99%
“…Self-organized structures called laser-induced periodic surface structures (LIPSS) have recently been discovered; the periods of such structures can be maintained constant and on the sub micro scale [8], and thus these structures could afford a new strategy for easy and cost-effective grating fabrication. In addition, LIPSS could be fabricated on virtually all materials, including metals [9], semiconductors [10], and dielectrics [11], which considerably expands the application range of gratings. Several parameters limit application of LIPSS, including uniformity, orientation, periodicity, and large-area consistency.…”
Section: Manipulation Of Lipss Orientation On Silicon Surfaces Using mentioning
confidence: 99%
“…Copyright (2018), AIP Publishing LLC. Reproduced from [12] ) of SWPSS ever achieved by fs and ns laser ablation, respectively. It was reported that a higher substrate temperature facilitates the formation of SWPSS and can trigger the evolution of LSFLs into SWPSS on silica when the substrate temperature exceeds 850 • C [11], which may explain the increase in the SWPSS period.…”
Section: Swpss On Snmentioning
confidence: 99%
“…Table 1 displays the reported scanning electron microscope (SEM) morphologies of SWPSS and summarizes the preparation conditions and the SWPSS periods. SWPSS is merely achievable on silica dielectrics [9][10][11][12] and silicon [13,14] by fs laser ablation in air (FLAA). Although SWPSS with periods in the range of 3-6.5 µm has been produced on chromium (Cr) and gold (Au) films using nanosecond lasers [15][16][17], no report has developed SWPSS on a metal target via fs laser ablation.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was transferred into a mathematical model by Sipe et al [ 30 ], being the almost widely accepted theory. Moreover, the surface scattered wave was later linked to surface plasmon polaritons [ 24 , 31 ]. The reasons and a fundamental theory for the creation of HSFL, however, are still under discussion [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%